1979
DOI: 10.1007/bf00389684
|View full text |Cite
|
Sign up to set email alerts
|

Das solit�re enchondrom

Abstract: Solitary enchondroma is a benign bone tumor with a doubtful prognosis changing by topical but not by clinical, roentgenological or histological characteristics. Therefore benign solitary enchondroma should be subdivided in such of peripheral and such of central localisation. Both forms of enchondroma normally show an asymptomatic development. Diagnostic problems occur in central enchondroma because of its radiological, angiographical and szintigraphical aspects. Peripheral enchondroma should be treated by loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Again, in MeCN, a significant intramolecular fluorescence quenching was observed in the triads, confirming that the photophysics is not dependent on the excitation wavelength, as expected from the highly efficient SSET. The thermodynamics of fluorescence quenching by electron transfer (Δ G PET ) can be calculated using Equation (1), where E ox is the oxidation potential of a related donor (diethylamine, +1.01 V),7 E red is the reduction potential of the acceptor (2‐methoxynaphthalene, −2.60 V),8 E 0‐0 is the singlet energy of the triads (85 kcal mol −1 ) determined from the intersection between the normalized excitation and emission bands, and ε is the relative permittivity of the solvent (1.9 and 37.5 for n ‐hexane and MeCN, respectively) 9. The analogous PET process with NP as acceptor does not have to be considered owing to an efficient and therefore fast SSET…”
Section: Resultsmentioning
confidence: 79%
“…Again, in MeCN, a significant intramolecular fluorescence quenching was observed in the triads, confirming that the photophysics is not dependent on the excitation wavelength, as expected from the highly efficient SSET. The thermodynamics of fluorescence quenching by electron transfer (Δ G PET ) can be calculated using Equation (1), where E ox is the oxidation potential of a related donor (diethylamine, +1.01 V),7 E red is the reduction potential of the acceptor (2‐methoxynaphthalene, −2.60 V),8 E 0‐0 is the singlet energy of the triads (85 kcal mol −1 ) determined from the intersection between the normalized excitation and emission bands, and ε is the relative permittivity of the solvent (1.9 and 37.5 for n ‐hexane and MeCN, respectively) 9. The analogous PET process with NP as acceptor does not have to be considered owing to an efficient and therefore fast SSET…”
Section: Resultsmentioning
confidence: 79%
“…Comparison of surrogate drop scenarios in this study to cadaver drop studies 26,27 indicates that linear fracture may occur in the infant from head-first fall heights 0.9 m onto carpet and 0.6-0.9 m onto concrete. However, due to the assumptions made when comparing the measured surrogate loads to cadaver data, the impact force data from this study and our previously published skull tissue response and threshold data will be used in a validated infant head computational model to predict the probability of skull fracture in occipital head-first falls from 0.3-0.9 m onto concrete, carpet pad, and mattress.…”
Section: Discussionmentioning
confidence: 85%
“…Linear fractures occurred in all 15 cadavers, regardless of surface. In a continuation of his previous work, Weber 26 dropped an additional 35 infant cadavers from the same height (0.8 m) onto 1 of 2 surfaces: a 2-cm foam mat and an 8-cm folded camelhair blanket. Only 2 of the 10 drops onto the foam mat and 4 of 25 drops onto the camelhair blanket resulted in linear fractures.…”
Section: Impact Force and Predictions Of Skull Fracturementioning
confidence: 98%
“…Most importantly, we have shown that solvent polarity can play an important role in stabilising the vicinal and distal CS states to a different extent, favouring a charge shift over the terminal units. Remarkably, this can be predicted with a good level of precision by the conventional Weller treatment of the electrochemical data 31…”
Section: Resultsmentioning
confidence: 85%
“…The energy‐level scheme can be completed by adding the states corresponding to the CS state. This can be done by using the electrochemical data (Table 1) after correction for the Coulombic interaction and the ion solvation energy based on the Born dielectric continuum model 31. The latter accounts for the difference in the solvents in the electrochemical (CH 2 Cl 2 ) and photochemical (TL, CH 2 Cl 2 , and BN) determinations 32.…”
Section: Resultsmentioning
confidence: 99%